Serum levels of IL-17A and cathelicidin antimicrobial peptide LL37 in females with breast cancer - Al-Harbi, Ahmed Abdullah Ahmed; Shetawi, Asmaa Zaki; Al Zobair, Alya Abd Alaziz Najim (Medical Journal of Indonesia, 2025)
BACKGROUND Breast cancer (BC) is a leading cause of morbidity and mortality in women. Interleukin (IL)-17 and the antimicrobial peptide LL37 have been implicated in BC pathogenesis. This study aimed to assess their levels in women with BC and evaluate their correlation with molecular subclasses, clinical, and laboratory parameters. METHODS This study included 69 BC females and 35 healthy controls. Patients were classified based on metastatic status and molecular indicators. Serum IL-17A and LL37 concentrations were estimated using ELISA and compared across patient subgroups. The area under the curve (AUC) was analyzed to determine cut-off values, sensitivity, and specificity for their diagnostic potential in BC. RESULTS IL-17A and LL37 levels were notably higher in patients with BC than in controls (p<0.0001). LL37 levels were also higher in the metastatic than in the non-metastatic group and controls. IL-17A levels were considerably higher in patients with metastatic than in controls (p<0.0001), but did not differ significantly between metastatic and non-metastatic patients (p = 0.5573). Regarding diagnostic performance, LL37 showed an AUC of 0.989 (p<0.001) at the best cut-off value of 16.79 ng/ml, LL37 exhibited 95% sensitivity and 94% specificity, indicating diagnostic potential. IL-17A showed an AUC of 0.87 (p<0.001), with a best cut-off value of 15.11 pg/ml, 78.81% sensitivity, and 100% specificity. Both LL37 and IL-17A levels were correlated with each other (r = 0.284, p = 0.018). CONCLUSIONS Patients with BC had increased serum levels of IL-17A and LL37. Their estimation is important for the follow-up of patients with metastatic.